2022
DOI: 10.1021/acsinfecdis.2c00424
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Stimulator of Interferon Genes (STING) Agonists Induce a Cytokine-Mediated Anti-Hepatitis B Virus Response in Nonparenchymal Liver Cells

Abstract: Chronic hepatitis B (CHB) remains a major public health problem worldwide, with limited treatment options, but inducing an antiviral response by innate immunity activation may provide a therapeutic alternative. We assessed the cytokine-mediated anti-hepatitis B virus (HBV) potential for stimulating the cyclic GMP–AMP synthase–stimulator of interferon genes (STING) pathway using STING agonists in primary human hepatocytes (PHH) and nonparenchymal liver cells (NPCs). The natural STING agonist, 2′,3′-cyclic GMP–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…More specifically, innate immune evasion was halted and this led to the inhibition of HBV replication mediated by IFN-I secretion [ 149 , 207 ]. Additional in vitro studies using three different STING agonists, cGAMP, 3′,3′-c-di(2′F,2′dAMP) and its bis(pivaloyloxymethyl) prodrug, corroborated that the activation of STING promotes viral clearance in human hepatocytes and non-parenchymal liver cells [ 208 ]. Similar effects were seen with the use of the topoisomerase II inhibitor daunorubicin, which activated the cGAS/STING pathway in vitro, suppressing HBV production [ 209 ].…”
Section: Targeting the Cgas/sting Associated Immune Evasion Mechanism...mentioning
confidence: 99%
“…More specifically, innate immune evasion was halted and this led to the inhibition of HBV replication mediated by IFN-I secretion [ 149 , 207 ]. Additional in vitro studies using three different STING agonists, cGAMP, 3′,3′-c-di(2′F,2′dAMP) and its bis(pivaloyloxymethyl) prodrug, corroborated that the activation of STING promotes viral clearance in human hepatocytes and non-parenchymal liver cells [ 208 ]. Similar effects were seen with the use of the topoisomerase II inhibitor daunorubicin, which activated the cGAS/STING pathway in vitro, suppressing HBV production [ 209 ].…”
Section: Targeting the Cgas/sting Associated Immune Evasion Mechanism...mentioning
confidence: 99%
“…A TLR7 agonist (GS-9620) could activate interferon-stimulated genes (ISGs) and induce the production of IFN-a, as well as other cytokines and chemokines, which led to the clearance of HBV-infected cells (86). In phase 2 research, GS-9620 was well tolerated and safe in CHB patients, transcription of ISGs and serum cytokines was detected, and no clinically significant HBsAg decline was observed (102). Coincidentally, recent research has shown that HBV can disturb host cGAS DNA sensing to enhance the replication of HBV (103).…”
Section: Hbv-tg Mice Preclinicalmentioning
confidence: 99%
“…STING agonists play an important role as antivirals. A synthetic analog of 3’,3’-c-di(2’F,2’dAMP), 2’,3’-cyclic GMP-AMP, and its precursor pivaloyloxymethyl exert strong anti-hepatitis B virus (HBV) effects in primary human hepatocytes regardless of HBV genotype ( 104 ). Zhang X et al.…”
Section: Modulators Of the Cgas-sting Pathwaymentioning
confidence: 99%